EFFECT OF ANIMATED COMPUTER ASSISTED INSTRUCTION (ACAI) ON MALE AND FEMALE PRIMARY SCHOOL PUPILS’ ACHIEVEMENT IN MATHEMATICS IN ANAMBRA STATE (UNIZIK Journal of STM Education, 2025)
This study investigated the effect of Animated Computer-Assisted Instruction on the mathematics achievement of male and female primary school pupils in Anambra State, Nigeria. Two research question and two hypothesis guided the study .The study was carried out In Awka Education zone of Anambra state, Nigeria and the population of the study was 4,634 primary public school pupils in the Awka Zone. Multistage sampling technique was used to select the sample size of 125 (64 males & 61 females) primary six pupils from four government schools in Awka Education zone. The study adopts a quasi-experimental design involving 125 primary school pupils, divided into experimental and control groups. The experimental group received mathematics instruction using ACAI, while the control group is taught using conventional teaching methods. Pre-tests and post-tests was administered to both groups to assess the effectiveness of ACAI in improving mathematics achievement. Mathematics Achievement Test (MAT) was used for data collection. The instrument was validated and Kuder-Richard (K-R21) method was used to establish the reliability of MAT at 0.89 which was found to be reliable. Mean and standard deviation was used to answer the research questions while ANCOVA was used to test the hypotheses at 0.05 level of significanceThe finding revealed that there is significant difference between the mean achievement scores of male and female primary school pupils taught mathematics using ACAI in favour of female and there is significant difference in the interaction effect of gender and teaching method in mathematics achievement. Based on the findings recommendations were made, that educational policymakers and school administrators in federal and State should integrate Animated Computer Assisted Instruction into the primary school mathematics curriculum with adequate resource and the developers of ACAI programs should consider gender differences in learning preferences and needs. This can be achieved by including features in ACAI software that address these differences, ensuring that both male and female pupils can equally benefit from the technology.
Keywords: Mathematics, Gender, Animated Computer Assisted Instruction, Achievement, Conventional Method and Primary School